Is European NATO really free-riding? Patterns of material and non-material burden-sharing after the Cold War. Issue 4 (2nd October 2018) - Jakobsen, Jo
ABSTRACT: Does European NATO free-ride on America? This article uses a mixed-methods approach to explore developments after the Cold War. I investigate both "material" measures, such as military expenditure and troop numbers, and a "non-material" indicator that draws on survey data of the public's willingness to fight for their country. Results and conclusions are not univocal. On the one hand, European NATO members have generally reduced their military spending (relative to GDP), abolished conscription and downsized their military forces. Their citizens' self-reported willingness to fight has also been quite low after the Cold War, in particular in states that host US military bases. On the other hand, some of these developments can surely be explained by a decrease in threat perceptions in Europe. Trends changed markedly after Russia's 2014 annexation of Crimea, which moved many allies – in particular new NATO member states – to increase their defence efforts.